IMPLEMENTASI PENDIDIKAN AQIDAH DALAM PEMBINAAN SIKAP SISWA DI MI BANCONG - Nur Avia Lutfiana; Zamzam Mustofa (Muara Aksara: Jurnal Ilmiah Multidisipliner, 2021)
This study describes the implantation of moral aqidah learning related to the formation of student character. This study aims to reveal how to implement moral creed learning towards the formation or trainging of students’ character faced by educators, and descriptions of planning, applying and evaluating conflicts faced by moral creed educators. Data collection uses qualitative methods, this technique is used to collect data from observations and interviews. The conclusion of the study shows that the implementation of character education in the planning of moral aqidah subjects still characterizes learning preparation and has not distributed character learning preparation, implementation in the application is still conventional, character education learning in each learning process still leads to the same pattern between early learning and so on. Furthermore, even the application of character cultivation is not in accordance with the material taught by the moral aqidah educators. The implementation of character education at the assessment level has been carrid out, but only uses one technique, namely the observation technique without improving the role of moral aqidah education at MI Bancong, Madiun.